Effect of Mudharabah Financing toward Sellers Members' Income at BMT Usaha Artha Sejahtera Bojonegoro - Mar'ah, Ana Kholifatul; Purnomo, Joko Hadi; Hidayati, Niswatin Nurul (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This research aimed to determine whether there is an influence on mudharabah financing on the income of seller members at BMT Usaha Artha Sejahtera Bojonegoro. The population in this research were 120 seller members at BMT Usaha Artha Sejahtera Bojonegoro. Samples taken by the authors were 52 respondents with stratified random sampling technique. Data collection techniques used were questionnaires while data analysis techniques using simple regression analysis. The research instrument test used the classical assumption test and the statistical test is the t test (partial) and to measure the effect between the independent variable and the dependent variable. The results of this research indicated that financing with mudharabah agreement influenced member income seen from the t test (partial test) sig value of 0,000, so that the tcount > t table and sig value < 0.1 were positive, and there was a regression equation Y = 5,630 + 0,652, in which it showed the value of regression X coefficient of 0.652 thus if mudharabah financing increased one-unit, then income would rise by 0.652 assuming the other variables are in constant state.